Exploring wild rices for photosynthetic efficiency improvement in rice - Kanchan Jumrani; Dipti Ranjan Pani; Mridul Chakraborti; Mirza Jaynul Baig; Viswanathan Chinnusamy; Palanisamy Veeraya; Ritu Tiwari; Dhammaprakash P. Wankhede; Rajkumar Subramani; Kanakasabapathi Pradheep; Parimalan Rangan (Physiology and Molecular Biology of Plants, 2026)
Photosynthesis is a key determinant for plant productivity, understanding its genetic basis will aid its improvement. The photosynthesis trait is primarily measured in terms of carbon and light utilization, using gas exchange and chlorophyll fluorescence methods. We report in this study, the extent of variability for photosynthetic trait in wild rice relatives, comprising a total of 26 taxa (22 wild species), using an infrared gas analyzer. The scale of measures used were, PN (net photosynthetic rate), E (transpiration), gs (stomatal conductance), Ci (intercellular CO 2 ), Ci/Ca (ratio of intercellular to ambient CO 2 ), WUE (water use efficiency), CE (carboxylation efficiency), Fv′/Fm′ (ratio of variable to maximum fluorescence, photosynthesis efficiency), qP (photochemical quenching), qN (non-photochemical quenching), ΦPSII (quantum yield of photosystemII), and ETR (electron transport rate). These were subjected to variability (ANOVA and PCA) and association (correlation matrices and path analysis) studies. The maximum PN was observed in Oryza australiensis , followed by Oryza officinalis and Oryza barthii . Maximum qP was observed in Oryza latifolia which was at par with O . australiensis , and Oryza alta . Highest CE was observed in O . australiensis . The CE values for O . barthii , Oryza grandiglumis and O. latifolia were at par with O . australiensis . Transcriptomic analysis for flag leaf between APO, the high efficient photosynthetic genotype with indica rice cultivar BAM4234 revealed key candidate genes underlying photosynthesis traits. These findings underscore the value of wild species and their alleles in expanding the photosynthetic capacity of rice potentially using classical breeding approaches.